STRATEGI PEMBERDAYAAN KEWIRAUSAHAAN SANTRI PESANTREN SYEKH MANSHUR PANDEGLANG - Tubagus Syihabudin; Kosasih Kosasih (Cakrawala Pedagogik, 2022)
This study explores a strategy for empowering students who have uniqueness and many advantages. Pesantren currently provide learning about religion and entrepreneurship to equip and provide independence when returning to society. This study aims to analyze the entrepreneurial empowerment of students and analyze the strategy of the Pondok Pesantren Syekh Manshur Kalahang Pandeglang in empowering student entrepreneurs. The research method used is descriptive qualitative. While the data collection techniques used were observation, interviews, and documentation. The results of the study indicate that the entrepreneurial empowerment activities that are managed and developed by the pesantren are adapted to the environmental conditions of the pesantren, the facilities and infrastructure, and the capabilities of the pesantren